Learning Interconnection IPS In Elementary School With Modern Century Character Education - Eka Yusnaldi; Raysyah Putri Sitanggang; Ikhtiati Ikhtiati Ikhtiati (Edumaspul: Jurnal Pendidikan, 2022)
Education is primarily a conscious effort to develop the potential of learners optimally. character education, namely; child's personal forms, to become good human beings, citizens, and good citizens, so as to anticipate the symptoms of moral crisis and was instrumental in the framework of fostering the younger generations. Social science Education is a subject that examines the social life of the material is based on the study of history, geography, economics, sociology, anthropology and statecraft. Through learning in the social science can enter the values of character education materials into the handle links in the IPS study